Сюрень-І (Крим): загальний археологічний контекст і специфіка поселень носіїв індустрії раннього оріньяку типу кремс-дюфур - Демиденко, Ю.Е. (Археологія, 2002)
У статті з опорою на дослідження 1990-х років наведено дані про культурно-хронологічну послідовність ключової для Криму періоду близько 30-19 тис. років тому стоянки Сюрень-І та характер поселень її ранньооріньякського епізоду заселення. В статье рассматриваются данные о ключевой стоянке крымской предистории периода около 30-10 тыс. лет тому назад - стоянки Сюрень-1. Представлен общий археологический контекст стоянки, состоящий из семи периодов заселения. Дан анализ специфики поселений раннего ориньяка типа кремс-дюфур Сюрени-1. Эти поселения как неспециализированные и серийные «интенсивные по жизнедеятельности людей кратковременные лагеря» представляют паневропейскую адаптацию Homo sapiens ориньяка (36.5 - 30 тыс. лет тому назад) к ландшафтам предгорий Южной Европы. The article is devoted to the key site in the Crimean Prehistory for the time span са. 30 000--10 000 years В.Р. — Siuren-I rock-shelter. First, it is represented in the site’s overall archaeological context, which is composed of 7 occupational events. It is discussed the specific characteristics of Settlements of Early Aurignacian of Krems-Dufour type industry at Siuren-I. These occupations are non-specialized and serial «intensive short-term camps», representing the Pan-European Homo sapiens Aurignacian adaptation (36 500–30 000 years В.Р.) to the European Southern belt's foothills.